Two new guaiane-sesquiterpenes from the cultured lichen mycobiont of Diorygma pruinosum. (December 2022) - Do, Thanh-Hung; Aree, Thammarat; Nguyen, Huu-Hung; Nguyen, Hoang-Chuong; Vo, Thi-Phi Giao; Nguyen, Ngoc-Hong; Duong, Thuc-Huy
Abstract: Lichens and the mycobionts derived from lichen-source are believed to be a valuable source of bioactive compounds. Diorygma pruinosum is a native lichen in Vietnam. A mycobiont of Diorygma pruinosum was separated, then cultivated. Phytochemical data on this lichen and its cultured mycobionts are scarce. The present study described the isolation and structural elucidation of two new guaiane-type sesquiterpenes, namely pruinosone (1 ) and hydroxypruinosone (2 ). Their absolute chemical structures were elucidated by extensive 1D and 2D NMR analysis, high-resolution mass spectroscopy, electronic circular dichroism (ECD), and comparisons in the literatures . Compounds 1 and 2 were evaluated for alpha-glucosidase inhibition and antimicrobial activity. Graphical Abstract: ga1 Highlights: Phytochemical data on the cultured mycobiont of Diorygma pruinosum were investigated. Two new guaiane-type sesquiterpenes namely pruinosone (1 ) and hydroxypruinosone (2 ) were isolated. Compounds were evaluated for alpha-glucosidase inhibition and antimicrobial activity.